Electrochemically Assisted Cycloaddition of Carbon Dioxide to Styrene Oxide on Copper/Carbon Hybrid Electrodes: Active Species and Reaction Mechanism. Issue 38 (25th May 2022) - Li, Wenze; Qi, Ke; Lu, Xingyu; Qi, Yujie; Zhang, Jialong; Zhang, Bingsen; Qi, Wei
Abstract: A novel electrochemically assisted cycloaddition process is proposed, in which highly efficient coupling of CO2 with styrene oxide (SO) can be achieved to form styrene carbonate (SC) as a high‐value‐added product. A series of Cu catalysts with different morphologies and chemical states were fabricated on carbon paper (CP) by using in‐situ electrodeposition, and the sample with nano‐dendrimer structure was found to exhibit a relatively high activity of 74.8 % SC yield with 92.7 % SO conversion under gentle reaction conditions, thus showing its potential for practical applications. The relatively high electrochemically active surface area and charge transfer ability of dendrimer‐like Cu benefited the electrochemical reaction. In particular, the Cu 2+ species that were formed in situ during the reaction played a vital role in enhancing the activity and selectivity of the proposed Cu/CP hybrid catalyst. Cu 2+ atoms served as active sites that can not only electrochemically activate CO2 but also facilitate the ring opening of SO. Mechanistic analysis suggested that the reaction followed electrochemical and liquid‐phase heterogeneous paths, which provide a new green and sustainable route for efficient utilization of CO2 resources for fine chemical electrosynthesis. Abstract : Cu/carbon paper (Cu/CP) electrode catalysts were prepared according to an in‐situ electrodeposition method. They exhibited high activity in catalyzing the electrochemically assisted cycloaddition of CO2 to styrene oxide (SO) forming styrene carbonate (SC) as high‐value‐added product. Cu 2+ atoms served as the active sites, that not only activated CO2 electrochemically but also promoted the ring opening of SO in a liquid‐phase reaction.